SPECIFIC QUALITY REQUIREMENTS OF TRANSPORT SERVISES (Perner's Contacts, 2011)
The transport is a necessary component of meeting the transport needs of the population and economic activity. It involved in raising living standards of population and the proper and effective functioning of the economy and society. Therefore it is necessary to meet the transportation needs of the required level of quality. The financial crisis together with other factors causing the existence of a fundamental impediment to obtaining a permanent position in the global business market.
Keywords: quality; transport; transport services; human resources